ANALISIS PROFIL MODEL MENTAL, KONSEPSI, TROUBLESOME KNOWLEDGE, DAN THRESHOLD CONCEPT SISWA PADA MATERI IKATAN KIMIA MENGGUNAKAN TES DIAGNOSTIK MODEL MENTAL TWO-TIER (TDM-TWO-TIER) - Dian Hasanah, - (2022)
This study aims to obtain an overview of the mental model profile, conception, troublesome knowledge, and threshold concept of students on chemical bonding material using a two-tier (TDM-two-tier) mental model diagnostic test. This research is qualitative research with a case study design. The participants of this study were 37 students of class XI IPA from one of the public high schools in the city of Bandung. Students' answers on the two-tier TDM were analyzed to determine the profile of students' mental models. A total of 17%, 9%, 16%, and 58% of students with complete, partial, misconception, and inconsistent mental models respectively. The findings and discussion showed that most of the students still had misconceptions or held concepts whose rationale was unknown regarding the concepts in chemical bonding material. The seven concepts tested are; formation of ionic bonds, formation of covalent bonds, metallic bonds, the solubility of substances based on the type of bond, boiling and melting points of substances based on the type of bond, hardness of substances based on the type of bond, and electrical conductivity of substances based on the type of bond. The misconceptions found in this study include; ionic bonds are formed due to the sharing of electrons between atoms or the formation of electron clouds between ions; in the formation of covalent bonds the attractive force is greater than the repulsion between atoms; in metals there is a sharing of electrons or an electron cloud surrounding the molecules, all substances that dissolve in polar solvents are ionic compounds, substances with high boiling and melting points are metallic bonded substances, sodium chloride is very brittle because of its ions strongly bonded to crystals, sodium chloride and hydrogen chloride crystals can conduct electricity. In general, students' misconceptions are caused by the inability of students to understand the particles that make up the material. Analysis of the characteristics of the material shows that the seven concepts are troublesome knowledge for students and the concepts that are threshold concepts for students are the concepts of ionic bond formation and electrical conductivity of substances based on the type of bond.